Meta-Analysis of the Influence of the STEM-Based Project Based Learning (PjBL) Model on Science Learning - Yeni Agustin; Lufri; Ali Amran; Ellizar (CV. AFDIFAL MAJU BERKAH, 2022)
In science learning, the STEM approach has been combined with project-based learning. This is an easy way to introduce the STEM approach to science learning. STEM (Science, Technology, Engineering, and Mathematics)-based learning can train students in applying their knowledge to create designs as a form of solving environmental-related problems by utilizing technology. This study will analyze how much influence STEM education with the PjBL model has on student learning outcomes. This study uses a meta-analysis method by calculating the effect size. Research data was obtained from 50 national and international journals. That the results of the analysis of the influence of the STEM education integration PjBL meta model on learning outcomes based on class level found that the STEM education integration PjBL model gave the highest influence at the Junior High School level, namely with an effect size of 2.07, then Senior High School, namely with an effect size 1.42, and Elementary School with an effect size of 1.39. Meanwhile, the appearance of Higher Education is in the smallest height category, namely 0.86. This shows that the STEM education integration PjBL model is effective when used at all levels of education. Based on the subjects, it was found that mathematics was in the highest category with an effect value of 3.03, while chemistry was in the medium category with an effect size of 0.60. So it can be concluded that the effect size of the STEM education integrated PjBL model on learning outcomes in terms of subjects has a high effect.